Evaluating Synthetic Data Potential for 60 GHz FMCW Radar Simulations with Real Measurements - Reitz, Philipp; Maiwald, Timo; Franchi, Norman; Weigel, Robert; Lübke, Maximilian (11th Microwave and Radar Week, 2024)
A fully integrated simulation environment for an FMCW radar system in an indoor environment operating at 60 GHz has been proposed. The simulation of the entire signal processing chain, starting with a CST simulation of the antenna pattern and extending to the radar signal processing, enabled the demonstration of the radar hardware’s and the channel’s inherent properties. Measurements and simulations have revealed the inherent fluctuation paths of a human target by showing a variation of 10 dB in the reflection power of the human and 0.5 m in the range profile in measurements. The papers results could demonstrate that synthetic datasets can be considered valid alternatives in radar detection. The channel properties could be examined by investigating different up-tilt configurations, and problems such as ground reflections caused by side lobes and multipath propagation within the human target could be further investigated.<br
Keywords: radar cross section; FMCW radar; simulation and measurement; mm-wave